Deep data analytics for new product development - Paczkowski, Walter R. (London Routledge, 2020)
"This book presents and develops the deep data analytics for providing the information needed for successful new product development. Deep Data Analytics for New Product Development has a simple theme: information about what customers need and want must be extracted from data to effectively guide new product decisions regarding concept development, design, pricing, and marketing. The benefits of reading this book are two-fold.
Includes bibliographical references (pages 152-258) and index.
Keywords: New products; Big data; Quantitative research